Perspectives on Early Screening and Prompt Intervention to Identify and Treat Maternal Perinatal Mental Health. Protocol for a Prospective Multicenter Study in Italy - Cena, Loredana; Palumbo, Gabriella; Mirabella, Fiorino; Gigantesco, Antonella; Stefana, Alberto; Trainini, Alice; Tralli, Nella; Imbasciati, Antonio (Frontiers in Psychology, 2020)
Background: The most common mental disorders in women during the perinatal (antenatal and postnatal) period are depressive syndromes and anxiety syndromes. The global prevalence of maternal perinatal depression ranges from 10% to 20%, while the prevalence of perinatal anxiety ranges from 10% to 24%. The comorbidity of mood and anxiety disorders in perinatal women is common, reaching 40%. In Italy, a few studies have been undertaken to evaluate the prevalence of perinatal depression and anxiety, and there is still a scarcity of research and intervention programmes regarding primary prevention. Three of the main aims of this study are (1) to evaluate the prevalence of maternal perinatal depression and anxiety in a large sample of women attending healthcare centres in Italy; (2) to investigate the psychosocial risks and protective factors associated with maternal perinatal depression and anxiety; (3) to evaluate the effectiveness of a manualized psychological intervention (Milgrom, Martin and Negri, 1999) to treat perinatal depression; (4) to evaluate the psychometric properties of both the Edinburgh Postnatal Depression Scale and the Patient Health Questionnaire–9 in detecting perinatal depression; (5) to evaluate the influence of maternal depression and anxiety on the development of infant temperament. Methods: This is a prospective cohort study, which merges an observational design and a pre-post intervention design. The study includes a one-year recruitment period and a one-year follow-up period. The methodological strategy includes (1) self-report questionnaires on maternal depression, anxiety, health status, quality of life and psychosocial risks; (2) a self-report questionnaire to measure the infant’s temperament; (3) a clinical interview; (4) a structured diagnostic interview; (5) a psychological intervention. Discussion: The results of this study may contribute to our knowledge about prevalence of antenatal and postnatal depression and anxiety (during both the trimesters of pregnancy and the first six trimesters after birth) and about the effectiveness of early psychological intervention in the perinatal health services. Trial Registration: ISRCTN12733828 - Registered 20 may 2019 Keywords: Perinatal, Antenatal, Postnatal, Anxiety, Depression, Screening, Assessment, Psychological Treatment.